Reduced Antarctic Bottom Water overturning rate during the early last deglaciation inferred from radiocarbon records - Sifan Gu; Zhengyu Liu; Ning Zhao; Tianyu Chen; Jimin Yu; Jiaxu Zhang; Chengfei He; Sang Chen; Zhaoru Zhang; Lingwei Li; Alexandra Jahn (Nature Communications)
Abstract The rapid CO2 rise during the early deglaciation is often linked to enhanced ventilation by intensified Antarctic Bottom Water (AABW) overturning. The recorded radiocarbon ventilation seesaw during the early deglaciation, which describes improved Southern Ocean and reduced North Atlantic abyssal radiocarbon ventilation, has been interpreted as intensified AABW and reduced North Atlantic Deep Water convections. However, abyssal radiocarbon records also reflect changes in surface reservoir ages and interior water mass mixing. Using isotope-enabled simulations, we show that this seesaw results from weakened AABW overturning and decreased Southern Ocean surface reservoir age. With AABW occupying the abyssal ocean, weakened AABW overturning increases transit time, with the magnitude increasing northward. This transit time increase outpaced the declining $$Δ ^{14}C_{{atm}}$$ Δ 14 C a t m induced Southern Ocean surface reservoir age decrease in the abyssal North Atlantic, but not in the abyssal Southern Ocean, thus producing a radiocarbon ventilation seesaw. Our results suggest sluggish deep water overturning from both poles during the early deglaciation.